Relationship Between Hygiene Practices and Occurrence of Diarrhea among Under-Five Children: A Case of East Pokot Sub County - Muga, Miriam Adoyo; Tarus, Mary Chemutai; Bor, Wesley (African Journal of Nutrition and Dietetics, 2023)
Communicable diseases continue to persist in developing countries with diarrhea being one of the conditions that affect children under five years of age resulting in numerous morbidities and mortality. Despite the interventions that have been put in place, Kenya still had an estimated 14% of children with diarrhea in 2022. Consequently, there is still a need to determine the actual practices associated with diarrhea at the community level. This will ensure that community-specific interventions are developed to curb diarrhea. Therefore, this study sought to determine hygiene practices that are associated with diarrhea. The study employed a descriptive cross-sectional design, and Fisher’s formula was used to calculate a sample of 384 caregivers from East Pokot Sub-County. Both purposive, proportional, and simple random sampling were used to reach the determined sample size. All ethical approvals- ethical clearance from Baraton Research and ethics committee and a research permit from NACOSTI were sought before the commencement of the study and participants consented before recruitment into the study. All collected data was de-identified, cleaned, and analyzed using STATA version 24. The chi-square test and logistic regression were used to determine the relationship between hygiene practices and the occurrence of diarrhea. All data were presented in tables. Open defecation was 2.24 times more likely to result in diarrhea, hand washing equipment, washing hands after toilet use, helping the child to wash hands after visiting the toilet, and washing hands with soap were 0.25, 0.58, 0.59, and 0.56 times less likely to result to diarrhea before adjustment respectively. However, after adjustment, only open defecation AOR: 1.78 (0.94 – 3.37), hand washing facility AOR: 0.17 (0.10 – 0.30), and age of the caregiver for the categories above 25 years that is 25-30 years, 31-36 years and above 36 years remained significant at P=≤ 0.01, ≤ 0.10 and ≤ 0.05 respectively. This study, therefore, recommends health education on the detriments of open defecation while encouraging community members and most importantly young caregivers on the benefits of handwashing practices and supporting community members to build latrines for the safe disposal of fecal matter. Key Words: Open defecation, Hygiene practices, Under-five children